Объяснение:
1) Так как х² - 2х + 1 = (х - 1)², то просто домножаем и числитель, и знаменатель на (х - 1), получаем:
2х(х - 1) / (x - 1)²
2) Так как 64y² - 49x² = (8y - 7x)(8y + 7x), то домножаем и числитель, и знаменатель на -(7х + 8):
(-7х - 8у)/(64y² - 49x²)
Объяснение:
1) Так как х² - 2х + 1 = (х - 1)², то просто домножаем и числитель, и знаменатель на (х - 1), получаем:
2х(х - 1) / (x - 1)²
2) Так как 64y² - 49x² = (8y - 7x)(8y + 7x), то домножаем и числитель, и знаменатель на -(7х + 8):
(-7х - 8у)/(64y² - 49x²)
Объяснение: